Anaerobic corrosion of carbon steel in bentonite: An evolving interface. (15th July 2021) - Leupin, Olivier X.; Smart, Nick R.; Zhang, Zhidong; Stefanoni, Matteo; Angst, Ueli; Papafotiou, Alexandros; Diomidis, Nikitas
Graphical abstract: Highlights: Initial anaerobic corrosion rates of steel in bentonite outpace the diffusion of water. A hydrogen gas phase is temporarily formed close to the steel surface. Gas and the lack of water desiccate the bentonite resulting in shrinkage microfractures. Diffusing Fe 2+ is oxidized by sorbed oxygen and precipitates in the porespace. The safety relevant properties of bentonite are not jeopardized by steel corrosion. Abstract: Experimental evidence related to the interactions between steel corrosion and bentonite in deep geological repositories is reconsidered. The released Fe 2+ interacts with the smectite and precipitates as Fe 3+ when oxidised by residual immobile oxygen. This leads to the development of coloured fronts in the bentonite. The evolution of these fronts can be reproduced by a reactive transport model that takes account of the competition between diffusion and precipitation. Furthermore, two-phase flow modelling indicates that the consumption of water by the corrosion outpaces the diffusion of water through the bentonite, leading to shrinkage microfractures in bentonite that act as preferential pathways for corrosion products.